Filtração de gases: estudo do fenômeno da limpeza por blocos - Tieni, Érica Flávia (Universidade Federal de São Carlos, 2005)
This work had for purpose to study the phenomenon of patchy cleaning in the operation of the gas filtration, which happens when there is the incomplete regeneration of the filter. A parameter very used to characterize this henomenon it is the cleaned fraction, which is defined as the ratio between the cleaned areas to the total area of filtration. In order to investigate the atchy cleaning behavior, filtration experiments were accomplished, with the intention to study the action of the cleaning in the fabric of polyester, for different combinations of experimental conditions. To characterize the cleaning for blocks, it has been developed a methodology that includes imagining of the blocks and computer program that analyzes these images of the cake at the end of each cleaning cycle. Using these images it was possible to mark the areas removed with the aim to obtain the size of the removed blocks. The general results showed that: for the maximum pressure drop of 1960 Pa, the fabric presented saturation behavior starting from the second filtration cycle, and for the maximum pressure drop 2939 and 3919 Pa, starting from the fourth filtration cycle. Unlike what was expected, the maximum cleaning velocity was not the one that gives the maximum removal of the cake. The residual pressure drop showed relationship with the distribution of the sizes of the removed blocks. Concerning the quantification of the removed blocks, the removed total area did not present defined behavior with the number of cycles. The largest percentage of the removed blocks presented size between 0,1 e 1 cm2. The area fractions and mass fractions removed presented curves with similar behavior. Besides, the two fractions presented very close values to each other, showing that the technique proposed in this work of quantification of the size of the removed areas presented quite satisfactory results.
Keywords: Filtros de tecido; Limpeza por blocos; Fração de limpeza; Remoção de torta; Perda de carga residual; ENGENHARIAS::ENGENHARIA QUIMICA